Air pollutants and ovarian reserve: a systematic review of the evidence - Zupo, Roberta; Castellana, Fabio; Nawrot, Tim S.; Lampignano, Luisa; Bortone, Ilaria; Murgia, Ferdinando; Campobasso, Gianluca; Gruszecka Kosowska, Agnieskza; Giannico, Orazio Valerio; Sardone, Rodolfo (Frontiers in Public Health, 2024)
Background Growing evidence indicates an association between ambient air pollution and decreased human reproductive potential. This study aims to systematically review the association between air pollutants and female ovarian reserve. Methods The literature was searched in six electronic databases through June 2024. Screening the 136 articles retrieved for inclusion criteria resulted in the selection of 15 human observational studies that evaluated the effect of environmental pollutants on ovarian reserve markers. The study protocol was registered on the International Prospective Register of Systematic Reviews (PROSPERO, registration code: CRD42023474218). Results The study design of the selected studies was found to be cross-sectional (2 of 15), retrospective cohort (10 of 15), prospective cohort (2 of 15), and case–control (1 of 15). The study population was distributed as follows: Asians (53%, eight studies), Americans (33%, five studies), and Europeans (14%, two studies). The main findings showed a higher body of evidence for the environmental pollutants PM2.5, PM10, and NO2, while a low body of evidence for PM1, O3, SO2, and a very low body of evidence for benzene, formaldehyde, and benzo(a)pyrene, yet consistently showing significant inverse association data. The overall methodological quality of the selected studies was rated moderated across the 14 domains of the National Institutes of Health (NIH) toolkit. Conclusion The data suggest that increased exposure to air pollutants seems to be associated with reduced ovarian reserve, with the most substantial evidence for pollutants such as PM2.5, PM10, and NO2. However, more evidence is needed to draw conclusions about causality.